Synthesis and Electropolymerization of Bis(phenylthieno[3, 2-b]thiophenes)– (4, 4'-dinonyl-2, 2'-bithiazole) co-monomer. (20th December 2016) - Sezer, E.; Osken, I.; Cinar, M.E.; Demirel, O.; Ustamehmetoğlu, B.; Ozturk, T.
Abstract: Synthesis of comonomer possessing 4, 4′-dinonyl-2, 2′-bithiazole and 3-phenylthieno[3, 2- b ]thiophene units (PhTT-NBT-PhTT ) was performed under Stille cross coupling condition. Its electropolymerization was conducted in the presence of trifluroborate–diethyl ether (BF3 · DEE) to lower the electrochemical polymerization potential through a complex formation between heteroaromatic monomers and boron trifluoride. Electrochemical properties of obtainedP[PhTT] andP[PhTT-NBT-PhTT] films, such as effect of electrolyte, polymerization charge, potential limits on the redox behaviour were investigated. They were further characterized by UV-visible spectrophotometric measurements. Corresponding electrical equivalent circuit was applied to the experimental electrochemical impedance spectroscopy (EIS) data to explain the parameters of each element and the interface between thePt/P[PhTT]/BF3 · DEE andPt/P[PhTT-NBT-PhTT]/BF3 · DEE systems. The band gap ofP[PhTT-NBT-PhTT was obtained as 2.04 eV by in-situ spectroelectrochemical measurements. Frontier molecular orbitals and electropolymerization of the comonomer were assessed computationally.